Text Complexity Modulates Cross-Linguistic Sentence Integration in L2 Reading - Leon Guerrero, Sibylla; Whitford, Veronica; Mesite, Laura; Luk, Gigi (Frontiers in Communication, 2021)
Cross-linguistic influences (CLI) in first-language (L1) and second-language (L2) reading have been widely demonstrated in experimental paradigms with adults at the word and sentence levels. However, less is known about CLI in adolescents during naturalistic text reading. Through eye-tracking and behavioral measures, this study investigated expository reading in English in adolescents speaking English as first and primary language and adolescents speaking Spanish as L1 and English as L2. In particular, among those L1 Spanish-speaking adolescents, we examined the role of L1 (Spanish) sentence integration skills when L2 school texts contained challenging syntactic structures, such as complex clauses, elaborated noun phrases, and anaphoric references. Results of generalized multilevel linear regression modeling demonstrated CLI in both offline comprehension and online eye-tracking measures that were modulated by school text characteristics. We found a positive relationship (i.e., facilitation) between L1 sentence integration skills and L2 English text comprehension, especially for passages with greater clause complexity. Similar main, but not modulatory, effects of sentence integration skill were found in online eye-tracking measures. Overall, both language groups appeared to draw upon similar reading component skills to support reading fluency and comprehension when component skills were measured only in English. However, differential patterns of association across languages became evident when those skills were measured in both L1 and L2. Taken together, our findings suggest that bilingual adolescents' engagement of cross-linguistic resources in expository reading varies dynamically according to both language-specific semantic knowledge and language-general sentence integration skills, and is modulated by text features, such as syntactic complexity.